Time-series pattern of gene expression profile in gentamycin-induced nephrotoxicity. (February 2014) - Qiu, Yunliang; Hong, Min; Li, Hua; Tang, Naping; Ma, Jing; Hsu, Ching-Hung; Dong, Wenxin
Abstract There have been many studies investigating the genomic biomarker and/or molecular mechanism of nephrotoxicity using microarray. However, most of these researches were carried out by studying gene expression changes at one specific time point. As gene expression varies with time and disease stage, the current study investigated the time-series pattern of gene expression in a rat model using a typical nephrotoxic compound. Rats were administrated with 80 mg/kg gentamycin or saline by intramuscular injection for 14 consecutive days followed by a 28-d recovery. Rats were scarified on D2, D4, D8, D15 and Recovery Day (R29), when kidneys were obtained for whole-genome microarray analysis and histological examination. Urine was collected at each necropsy for kidney injury molecular-1 (KIM-1) analysis. The KIM-1 detection and histological examination confirmed the nephrotoxicity. After differentially expression genes (DEGs) identification, there were 4360 and 4323 regulated genes for females and males, respectively. However, few overlapping expression genes co-regluated at each time point were found. By principle component analysis (PCA) and hierarchical cluster, the gene expression patterns were observed to be apparently associated with the disease stage. GO Annotation showed (1) immune response and related process, response to wounding, cell locomotion on D2; (2) cell death and apoptosis was also noted on D4; (3) processes of organic acid or carboxylic acid, apoptosis or cell death on D8 and D15; (4) processes of cell cycle, mitosis, division cell cycle on R29. In conclusion, the authors mapped the time-series gene expression patterns at the initiation, development and recovery stage of gentamycin-induced nephrotoxicity.